Sanksi Pelanggaran Kode Etik Notaris Oleh Majelis Pengawas Daerah - M. Jamil (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2018)
Notary is a function that is used from the state inthe field of private law and applies the role in makingauthentic deeds that have perfect proof power. Legalbasis for the implementation of the notary profession, inaddition to the Notary Act and other regulations, theNotary also has a Notary Code of Ethics as a foothold incarrying out his profession. In order to ensure tehcomplience in laws and codes of ethics, Notaries aresupervised by the regional supervisory board. Theexistence of a regional supervisory board is required tobe carried out professionally in carrying out their dutieswithout any feeling of discomfort for the monitorednotary. Notaries need more concrete objective laws,then the Notary Law and the Notary Code of Ethicsrespond to these concerns. However, the complience tothe ethics of the profession is very influential on themorals of the notary himself